The implications of contractualism for the responsibilisation of higher education. Issue 1 (2nd January 2017) - Rawolle, Shaun; Rowlands, Julie; Blackmore, Jill
ABSTRACT: Within the context of heightened perceptions of risk within the higher education sector worldwide, responsibility for outcomes is increasingly required not only of universities but, also, of individual academics. In turn, contracts have become a key form of governance for institutions in mediating and modulating this risk and responsibility. While much writing around the use of contracts in higher education has focused on market-based, competitive neoliberal conceptions of contractualism, this article argues that there are, in fact, two largely antagonistic new modes of contractualism – market contractualism and relational contractualism – and a third, residual mode, paternal contractualism. These three modes of contractualism coexist within universities, in tension. The article draws on two Australian exemplars to highlight how these tensions play out and to highlight the potential for contractualism to create spaces for shared goals and projects and shared risks resulting from the ways in which responsibility and individual agency are negotiated.